VERIFIKASI METODE PENENTUAN KADAR AMONIA SEBAGAI NITROGEN (NH3-N) DALAM SAMPEL AIR BERSIH DENGAN METODE HACH 8155 DI PT BADAK NGL BONTANG - Yusuf, Irfan Maulana; Pasaribu, Subur P.; Panggabean, Aman Sentosa (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
The research about method verification for determination of ammonia levels as nitrogen (NH3-N) in clean water samples using the Hach 8155 method at PT Badak NGL Bontang has been done. Method verification was carried out by testing several verification parameters such as linearity tests, determining of instrumentation detection limits, detection limits of the method, quantification limits, repeatability, reproducibility and accuracy. The research results showed that the linearity test had good results with a correlation coefficient (R2) was 0.9992; instrumentation detection limit value was 0.01 mg/L; method detection limit value was 0.01 mg/L; quantification limit value was 0.03 mg/L; the repeatability value obtained from %RSD is less than 2/3 of the Horwitz CV; reproducibility value was 0.497 obtained from the Zscore value with acceptance requirements, namely 1.96 ≥ Zscore ≥ -1.96; and the accuracy value of the measured levels was 0.483 with a concentration range limit of 0.364 – 0.533 mg/L. The research results show that the Hach 8155 method can be used as a routine analysis method at PT. Badak NGL. Keywords : Method verification, ammonia, clean water, Hach 8155 method.